2022
DOI: 10.1111/cge.14249
|View full text |Cite
|
Sign up to set email alerts
|

New Cerebellar Ataxia, Neuropathy, Vestibular Areflexia Syndrome cases are caused by the presence of a nonsense variant in compound heterozygosity with the pathogenic repeat expansion in the RFC1 gene

Abstract: The biallelic pathogenic repeat (AAGGG)400–2000 intronic expansion in the RFC1 gene has been recently described as the cause of cerebellar ataxia, neuropathy, vestibular areflexia syndrome (CANVAS) and as a major cause of late‐onset ataxia. Since then, many heterozygous carriers have been identified, with an estimated allele frequency of 0.7% to 4% in the healthy population. Here, we describe in two affected CANVAS sisters the presence of the nonsense c.724C > T p.(Arg242*) variant in compound heterozygosity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…CANVAS arises from a polymorphic set of biallelic RFC1 repeat expansion motifs comprising AAGGG, AAAGG, ACAGG, AAGGC, AGGGC, and AGAGG motifs in isolation or as heterozygous combinations 8,9,11,12 . Further, rare CANVAS patients harbor compound heterozygous monoallelic RFC1 expansions combined with loss-of-function mutations that result in RFC1 haploinsufficiency from the nonexpanded allele [17][18][19] . This, in combination with data indicating a recessive mode of inheritance, suggested to us and others that RFC1 loss-of-function is a pathogenic driver of CANVAS pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CANVAS arises from a polymorphic set of biallelic RFC1 repeat expansion motifs comprising AAGGG, AAAGG, ACAGG, AAGGC, AGGGC, and AGAGG motifs in isolation or as heterozygous combinations 8,9,11,12 . Further, rare CANVAS patients harbor compound heterozygous monoallelic RFC1 expansions combined with loss-of-function mutations that result in RFC1 haploinsufficiency from the nonexpanded allele [17][18][19] . This, in combination with data indicating a recessive mode of inheritance, suggested to us and others that RFC1 loss-of-function is a pathogenic driver of CANVAS pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies suggested that RFC1 mRNA and protein expression are unaltered in the context of the repeat expansion, which is inconsistent with the classical mechanism by which recessively inherited repeat expansions elicit a loss of function for the genes in which they reside 8,10,15,16 . However, identification of rare compound heterozygotic CANVAS patients harboring RFC1 truncating and splicing loss-of-function mutations with single allele repeat-expansions suggests a role for RFC1 function in CANVAS [17][18][19] . Alternatively, the repeats could potentially elicit toxicity through dose-dependent gain of function mechanisms (such as repeat associated non-AUG initiated (RAN) translation or repeat RNA-protein complex formation) that only manifest in homozygosity or in combination with RFC1 haploinsufficiency 20,21 (Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Biallelic expansions of (A 2 G 3 ) n repeats cause a newly discovered repeat expansion disease (RED) named CANVAS ( c erebellar a taxia, n europathy, v estibular a reflexia s yndrome) ( 1 , 2 ). It is an autosomal recessive disease with a carrier frequency range from 0.7% to 4% in studied populations, resulting in a prevalence range from 1:20 000 to 1:625, respectively ( 1 , 3 ). This frequency establishes RFC1 -related ataxia as likely the most common cause of hereditary late-onset ataxia ( 1 , 2 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given its essential role, it is not surprising that this is the first RFC1 mutation found to cause human disease. While the pathogenic mechanism of CANVAS remains uncertain, RFC1 loss of function is suspected due to (i) its recessive inheritance and (ii) the discovery of CANVAS-affected patients heterozygous for the repeat expansion and an RFC1 truncating mutation ( 3 , 8–11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the current data indicate that RFC1 expansions are likely the most frequent cause of recessive ataxias, and many patients remain undiagnosed. 10 , 16 More recently, the genotype spectrum of RFC1 -related disease has been expanded by identifying truncating, frameshift, and nonsense variants in compound heterozygosity with an AAGGG expansion. 14 , 16 , 17 Regarding the disease pathophysiologic mechanism in the case of homozygous expansions, it proved to be puzzling and remains undetermined.…”
Section: Introductionmentioning
confidence: 99%